Free glycerin determination in ethanol biodiesel utilizing spectrophotometric and chromatographic (GC/FID) methods - Louzeiro, Hilton Costa; Soledade, Luiz Edmundo Bastos; de Souza, Antonio Gouveia; Maciel, Adeilton Pereira; Silva, Fernando César (Eclética Química, 2015)
According to the Resolution number 7 from the Brazilian National Agency of Oil, Natural Gas and Biofuels (ANP), the official methodologies for free glycerin determination in biodiesel are the ASTM D 6584, EN 14105 and EN 14106 methods. However, these procedures are limited to the analysis of free glycerin in methyl esters and they are not suitable for the analysis of esters from lauric oils. In the present work, a gas chromatographic method was developed for the determination of the amount of free glycerin in ethyl esters from lauric oils, aiming at overcoming the limitations present in the official methods. Moreover, the present method can also be used for ethanol and methanol biodiesel samples from other oily sources. Besides, a methodology that ascertains the content of free glycerin by UV-Vis spectrophotometry was also applied. Both methods were sensitive enough to determine the content of free glycerin in biodiesel, below the limit specified by the ANP, fixed at 0.02 % (200 mg/L), achieving the detection limits of 5.69 mg/L and 2.17 mg/L for the chromatographic and spectrophotometric methods, respectively.